RELATION OF AGE AND PROSTATE VOLUME ON PROSTATE SPECIFIC ANTIGEN LEVELS IN PATIENTS WITH BENIGN PROSTATE HYPERPLASIA - DR. A. BHAGYA LAKSHMI; DR. CH. KALAVATHI (International Journal of Pharma and Bio Sciences, 2015)
Prostate specific antigen is not cancer specific, if can be elevated in patients with benign prostate hyperplasia (BPH). The blood sample from 80 BPH patients are estimated for PSA and the values are compared with patient’s age and prostatic volume. The mean PSA for the age groups 40-50 yrs, 51-60 yrs, and 60-70 yrs and > 70 yrs were 0.9ng/ml, 1.6ng/ml, 3.2ng/ml and 4.8ng/ml respectively. The increased PSA levels are also raised along with prostatic enlargement. The size of prostate is < 30gm, 31-40gm, 41-50gm and >50gm corresponded to mean PSA values of 0.9ng/ml, 1.6ng/ml, 3.2ng/ml and 4.8ng/ml respectively. In conclusion, there is marked and significant influence of age and prostate volume on serum PSA levels. The older the patient and the largest is his prostate volume, the higher the PSA serum level.